Correlation Between Job Satisfaction Level and Workstation Design: A Survey at Malaysian Automotive Industry - Isa, Halim (The Institution of Engineers, Malaysia, 2011)
Automotive industry has been recognized as one of main contributors to nation economy as it offers enormous job opportunities. The workstation in automotive industry should be designed ergonomically so that their operators could perform jobs safely and productive. The objectives of this study is to obtain the level of job satisfaction of production operators with respect to their workstation design. A questionnaire survey was conducted among 210 production operators at four automotive industries in Malaysia. The survey concluded that majority production operators satisfied with the current design of their workstation. In addition, convenience to move in the workstation has been identified as a vital contributor to the satisfaction.